2014
DOI: 10.2190/iq.34.3.e
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Stigma and Persons Living with HIV/AIDS in Rural Ghana

Abstract: This qualitative study investigated community and family members' perceptions and attitudes toward persons living with HIV/AIDS (PLWHAs) in rural Ghana and how PLWHAs viewed themselves. The purpose was to provide insights into the nature and extent of HIV/AIDS-related stigma for program and policy interventions. Interviews and focus group discussions examined the stigma. Seventy-four participants 18 years and above (60 community members, 10 PLWHAs, 2 family members of PLWHAs, and 2 HIV/AIDS counselors) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…3,10 Other forms of stigma and discrimination against PLHIV include blaming and ostracism by individuals and community members; and yet many PLHIV hold strong negative concepts about themselves. 11 These then affect the health seeking behaviour of PLHIV, and even those who do not know their HIV status are pushed away from voluntary counseling and testing. HIV positive people may therefore not seek HIV services early for fear of being labeled, mocked, abused and ostracised.…”
Section: Introductionmentioning
confidence: 99%
“…3,10 Other forms of stigma and discrimination against PLHIV include blaming and ostracism by individuals and community members; and yet many PLHIV hold strong negative concepts about themselves. 11 These then affect the health seeking behaviour of PLHIV, and even those who do not know their HIV status are pushed away from voluntary counseling and testing. HIV positive people may therefore not seek HIV services early for fear of being labeled, mocked, abused and ostracised.…”
Section: Introductionmentioning
confidence: 99%
“…Many prevention efforts have focused on increasing transmission knowledge in order to address misconceptions that may stymie improvements in behaviour toward healthy practices and to reduce stigma against people living with HIV/AIDS (Kingoum & Akoachere, 2016;Peltzer et al, 2007;Rogers et al, 2006). It has been demonstrated that stigmatizing attitudes are closely related to HIV transmission misconceptions and negative attitudes toward people living with HIV (Ana et al, 2013;Mumin et al, 2018). An assessment of KAPs in any population is critical for HIV management and prevention planning, as well as for evaluating the effectiveness of prevention strategies (Kingoum & Akoachere, 2016 This study focuses on pregnant women because women account for 65% of people living with HIV in Ghana, and they are generally at higher risk of new infection than men (Ghana AIDS Commission, 2017; UNAIDS, 2014).…”
Section: Introductionmentioning
confidence: 99%